The invisibility of women in scientific articles on vigorexia - Stein, Fabiana Loréa Paganini (2021)
This article aims to analyze how women are placed in scientific articles on vigorexia. The empirical corpus consists of articles from Science Direct and Scielo.Org databases. These articles address the difference in the requirement of beauty in men and women bodies as a means to justify the emphasis on the study of vigorexia in men, and the gender inequalities in physical activities were reaffirmed. This led us to problematize the regimes of truths engaged in power relations that produce subjects.